The Complete Folktales of A. N. Afanas'ev : Volume I - Afanasʹev, A. N. (Aleksandr Nikolaevich), 1826-1871 (Book collections on Project MUSE., 2014)
The first volume of comprehensive gathering of tales from the Russian Grimm.